Literasi Keuangan Pedagang Di Taman Wisata Makam Sunan Giri Gresik - Bangkit Widi Utomo, Anang; Agus Santoso, Rahmat (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to test the Financial Literacy of Traders at the Taman Wisata Makam Sunan Giri Gresik through 4 aspects of financial literacy, namely financial knowledge, savings and loans, insurance, and investment. By collecting data from 5 (five) informants, one of which is a key informant as the main resource or opening the way in this research. The test was conducted using qualitative research methods. The test was carried out using data analysis of the Milles and Huberman model which includes data collection, data reduction, data presentation, and verification. The results show that the Financial Literacy of Traders at Taman Wisata Makam Sunan in the aspect of financial knowledge through recording, planning, and spontaneity. The savings held by traders are used for urgent and unexpected purposes, which amount to around 20% of the profits earned. Loans made by traders are used for capital based on an assessment of the amount of installments and interest. The insurance owned by the traders is only in the form of health insurance used for their families, they do not register their businesses because they are only small businesses. In the investment aspect, traders mean that investment has benefits and added value for survival in the future.